ANALISIS POLA PENGELOLAAN LAHAN PERTANIAN DI SEKITAR MEANDER LUK ULO KECAMATAN KARANGSAMBUNG KABUPATEN KEBUMEN (Forum Ilmu Sosial, 2016)
The aim of this research is to know the characteristic of meander and pattern management on agricultural farm in around the Meander of Luk Ulo's river. Observational location is at Luk Ulo's River Karangsambung's district kebumen's Regency,  observational region is divided as 2 regions which is segments 1 and segments 2, interview sample is done with purposive sampling method with determination sample of slovin's formula, gotten as much for about 86 farmers. This research uses descriptive research method. The result of this research to explain the pattern management of farm on segment 1 as monoculture, meanwhile for rotation of the plant, farmers still choose padi-padi-bera, meanwhile for padi-padi-palawija is decrease, farmer generally use 2 times to rotate their plants, farmers choose stool terrace because inclination bevels that steep enough, irrigation system which uses is rain tank (tadah hujan), management pattern of the farm on segment 2 monoculture, to rotate the plant is padi-padi-bera, and rotate the padi-padi-palawija is decrease, for farm conservation, farmers in this region generally uses causeway terrace or (pematang sawah) and doesn't use mulch, irrigation in this region is technical irrigation whereas for effortkeeps up river's environment, society on segment 2 haven't done effort keeps up river environment.